Sway control of a tower crane with varying cable length using input shaping - Haszuraidah, Ishak; Zaharuddin, Mohamed; Fasih, S.M.; Bello, M.M.; Reza Ezuan, Samin; Adebayo, B.W. (Springer Nature, 2024)
This paper presents the development of input shaping techniques for effective sway control of a tower crane, considering varying cable lengths. The nonlinear dynamic model of the tower crane is derived using the Lagrange equation, and simulations confirm its close agreement with experimental results. To design and assess the input shaping control schemes, an unshaped square-pulse input is initially employed to determine the system’s characteristic parameters. Zero Vibration (ZV) and Zero Vibration Derivative (ZVD) shapers are specifically devised based on the tower crane’s inherent properties, and their performance is examined under various operating conditions, encompassing payload hoisting scenarios. The effectiveness of these shapers is evaluated through criteria such as maximum oscillation and reduction of mean squared error (MSE) for overall oscillations. The outcomes of this study demonstrate that implementing input shapers can offer practical and advantageous solutions for enhancing tower crane performance and ensuring smoother operation.